Micromechanical modeling and experimental analysis of yarn separation type sewing damage on continuous filament fabrics - Cui, Lina; Weng, Chengwu; Liu, Gui; Huang, Canyi; Liu, Fanxizi; Zhang, Yinjia; Qiu, Yiping; Zhang, Chuyang (Textile Research Journal, 2023)
Fabrics with weaves of low interlacing density and smooth yarns such as continuous cuprammonium filaments are often susceptible to sewing damage of cracks perpendicular to the sewing line, seriously influencing the aesthetics of the finished garment. To understand how the important factors such as yarn modulus, yarn bending stiffness, sewing needle radius, yarn-on yarn-friction, fabric counts and fabric weaves act on the crack length of such a fabric, a micromechanical model is proposed, and the experimental results are compared with the theoretical prediction. Single yarn pull-out tests and single yarn axial compression tests are performed to estimate yarn-on-yarn friction and yarn bending stiffness, respectively. The model indicates that the sewing crack length is positively proportional to the yarn tensile modulus, yarn bending stiffness and the needle radius and is negatively proportional to the fabric count and the inter-yarn friction. The model predicted crack lengths are within the range of the experimental results in warp direction while the predicted value is substantially larger than the observed crack lengths in weft direction due to the high compressibility of the weft yarn, which decreased yarn tension, bending stiffness and increased yarn cover power. For a given fabric, increasing yarn-on-yarn friction and raising yarn compressibility is an effective way to control the crack lengths.